Pengaruh Perbandingan Tempe dan Puree Daun Kelor (Moringa Oleifera L.) Terhadap Karakteristik Nugget - Sianturi, Rut Elisabet; Mayun Permana, I Dewa Gde; Timur Ina, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 2 (2022): Jurnal ITEPA, 2022)
This research was conducted with the aim of knowing the effect of the comparison of tempeh and puree moringa leaves on the characteristics of the nuggets and to find out the correct ratio so as to be able to produced nuggets with the best characteristics. The Completely Randomized Design (CRD) was used in the research with a treatment ratio of tempeh and puree moringa leaves wich consist of 5 levels: 100%: 0%; 95%: 5%; 90%: 10%; 85%: 15%; 80%: 20%. The treatment was repeated 3 times to obtain 15 units of the experiment. The data obtained were analyzed by variance and if the treatment had an effect on the observed variable then continued with Duncan’s Multiple Range Test (DMRT). The result showed data that tempeh and puree moringa leaves had a very significant effect on water content, ash content, fat content, protein content, carbohydrate content, vitamin C, antioxidant activity, color (hedonic), texture (hedonic and scoring), aroma (hedonic), taste (hedonic and scoring), and overall acceptance (hedonic) of nuggets. Comparison of 80% tempeh: 20% puree moringa leaves produced nuggets with the best characteristics, specifically: water content 54.62%, ash content 2.37%, fat content 11.57%, protein content 15.13%, carbohydrate content 16.32%, Vitamin C 4.67 mg/g, antioxidant activity 50.78%, color liked, texture mushy and liked, aroma normal, taste liked and overall acceptance liked.